John for Everyone: Part 2, Chapter 11-21 - Wright, N. T. (Nicholas Thomas); Sharpe, Sally D., 1964- (London SPCK, 2002)
"A guide to John that includes helpful commentary and full translation of the text by Tom Wright, this twentieth anniversary edition also contains study guide materials to assist readers in using the book for group study, personal study, or daily devotions"--
part 1. Chapters 1-10 -- part 2. Chapters 11-21.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible. -- Commentaries; Gospel of John - Commentary; Gospel of John - Interpretation and Criticism; Commentaries